Exploring adenosine analogs for chondrosarcoma therapy: In vitro and in vivo insights - Marion Lenté; Juliette Aury-Landas; Mahdia Taieb; Benoît Bernay; Eva Lhuissier; Karim Boumédiene; Catherine Baugé (Molecular Therapy: Nucleic Acids)
Chondrosarcomas (CSs) are resistant to conventional chemotherapy and radiotherapy. Therefore, new therapeutic approaches are needed. The aim of this study was to validate the use of adenosine analogs as a new therapeutic strategy for the treatment of CS. Five adenosine analogs (aristeromycin, cladribine, clofarabine, formycin, and pentostatin) were evaluated in vitro on CS cell lines via both (two-dimensional) 2D cultures and three-dimensional (3D) alginate bead models. Cell viability was assessed by cell counting or ATP assays. Apoptosis was measured and cell cycle analyzed. The most promising compounds were further tested in vivo using a xenograft CS model in nude mice. Four analogs significantly reduced the viability of CSs. Among these, cladribine and clofarabine demonstrated potent efficacy in both 2D and 3D models by inducing apoptosis. Cladribine was further found to induce cell-cycle arrest, leading to apoptosis-mediated cell death. In vivo, both cladribine and clofarabine exhibited substantial antitumor effects in a xenograft model. In conclusion, cladribine and clofarabine, which have already been approved for clinical use in leukemia and multiple sclerosis, are promising candidates for the treatment of CS. Their efficacy in preclinical models suggests that these molecules could be repurposed for phase 2 clinical trials in patients with CS.